(untitled) (European Journal of Pure and Applied Mathematics, 2025)
We introduce a new transform called the conformable double Sumudu-Shehu transform. It helps solve fractional partial differential equations that appear in physical and engineering problems. The transform uses the conformable derivative idea. We explain its basic properties and show how it works. Then we apply it to some well-known equations like the wave and Klein-Gordon equations.